Automotive fuel cell engine test cell design and its thermal flow analysis. (6th September 2018) - Zhang, Xinfeng; Luo, Minghui; Dai, Wei; Yao, Chuanqi; Wang, Jiwen; Huang, Daojin; Wang, Chunyang
Abstract: A test cell for automotive PEM fuel cell engine is introduced and designed. Similarities and differences of facilities between PEM fuel cell engine and inner-combustion engine are illustrated. It turns out that, the air treatment, exhaust gas, cooling and electrical facilities are quite similar, the fuel treatment, power load type, ventilation and air-conditioning are quite different, while the vibration isolation and noise elimination facilities are completely simplified. Furthermore, a thermodynamic model is proposed to analysis the heat flow in fuel cell engine test cell. The Monte Carlo Simulation method is applied to get the proportion of outgoing thermal flows. A thermal flow rule of 4.5/4.5/0.6/0.4 is proposed as rule of thumb for cell designer. Highlights: Test facilities for FCE are similar or simplified compared to these for ICE. Cell's energy flows are electrical power, coolant, exhaust and ventilation. Heat flow proportion of the testing cell is 4.5/4.5/0.6/0.4.